2014
DOI: 10.1155/2014/671532
|View full text |Cite
|
Sign up to set email alerts
|

Drug Release Kinetics and Front Movement in Matrix Tablets Containing Diltiazem or Metoprolol/λ-Carrageenan Complexes

Abstract: In this work we investigated the moving boundaries and the associated drug release kinetics in matrix tablets prepared with two complexes between λ-carrageenan and two soluble model drugs, namely, diltiazem HCl and metoprolol tartrate aiming at clarifying the role played by drug/polymer interaction on the water uptake, swelling, drug dissolution, and drug release performance of the matrix. The two studied complexes released the drug with different mechanism indicating two different drug/polymer interaction str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The formulation containing the highest ratio of kappa-carrageenan (CKH1) released 100% of ACV in 120 h, whereas the CKH2 formulation required 192 h to release all of the drug. This may be the result of the ability of the kappa-carrageenan compacts to erode, as has been described by Bettini et al [ 32 ] for the metoprolol/λ-carrageenan matrix. The chitosan-based compacts showed a strong interaction between chitosan and HPMC, and a more controlled release of ACV, regardless of the chitosan/HPMC ratio.…”
Section: Resultsmentioning
confidence: 79%
“…The formulation containing the highest ratio of kappa-carrageenan (CKH1) released 100% of ACV in 120 h, whereas the CKH2 formulation required 192 h to release all of the drug. This may be the result of the ability of the kappa-carrageenan compacts to erode, as has been described by Bettini et al [ 32 ] for the metoprolol/λ-carrageenan matrix. The chitosan-based compacts showed a strong interaction between chitosan and HPMC, and a more controlled release of ACV, regardless of the chitosan/HPMC ratio.…”
Section: Resultsmentioning
confidence: 79%
“…NA and CRG K were added to slow the ABX-CRGK complex dissociation, and CS served as a cross-linking agent. Different formulations were selected to check the impact of CS removal (F1), CRG K removal (F2), SA solid particles usage instead of its solution (F3), and the impact of combining the CRG K , CS, and SA solution to form F4 [ 26 , 27 ]. Furthermore, the selection and optimization of the SA, CS, and CRGK grades and amounts were based on having the ABX particles released as nanoparticles from the polymeric raft/floating gel [ 25 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that different drugs give complexes with quite different characteristics of solubility and drug release kinetics. In another approach, carrageenan was associated with two drug models, diltiazem HCl and metoprolol tartrate, and the two studied complexes released the drug with different mechanism indicating two different drug/polymer interaction strengths (stronger interaction with diltiazem) [ 259 ]. Other recent developments included the use of carrageenan, combined with other matrix materials, to associate and release vitamin B2 [ 260 ] and lisinopril [ 261 ].…”
Section: Drug Delivery Systems Based On Seaweed Sulfated Polysacchmentioning
confidence: 99%